The Knowledge Functionality in the Teachers’ Online Social Networks (TOSN) in UAE - AL-RASSOUL, ASHRAF SHAWKY (2019)
The issue of teachers' professional development is a challenge for educational systems and educational experts as a result of the rapid changes that occur in societies and affect the educational process. These changes including the tremendous development of communication technology, have led both educational institutions and self-motivated teachers to digital platforms in search of professional development. Formal platforms have been established by educational institutions, and informal platforms have been established on the social networks of teachers. This study examines the professional knowledge in the teachers' online social networks (TOSN) in terms of editing and exchanging. This study also seeks the factors affecting this knowledge in order to analyze these networks and evaluate the role in the teachers' professional development and recording the advantages of these communities for investing in future projects for the establishment of such platforms. The study found through the questionnaire that teachers accept these TOSNs because they provide them with professional development and achieve this goal better than traditional programs for professional development. The study has also found that this knowledge is applicable, which positively affects the outcomes of the educational process. One of the factors influencing the promotion of this knowledge is the encouragement of members in these communities to participate, the presence of trust among all members of society, use case-based learning style, possessing digital communication skills.